2015
DOI: 10.1007/s12094-015-1348-1
|View full text |Cite
|
Sign up to set email alerts
|

Serum nectin-2 levels are diagnostic and prognostic in patients with colorectal carcinoma

Abstract: Serum levels of nectin-2 may have diagnostic roles for CRC patients. Moreover, our study results show the prognostic role of nectin-2 in non-metastatic group patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 35 publications
0
21
0
Order By: Relevance
“…While the second CD226 ligand, nectin 2 or CD112, has been found to be overexpressed in many cancers including lymphoblastic leukemia and squamous cell carcinomas, one study also documents the presence of soluble nectin‐2 in sera of cancer patients. Baseline serum nectin‐2 levels were found to be elevated in patients with colorectal cancer, especially at the nonmetastatic levels . All these data show that the soluble isoforms of the immune checkpoint molecules can serve as important prognostic or diagnostic markers and also present with novel immunotherapeutic strategies in cancer.…”
Section: Immune Checkpoint Molecules: Regulating the Immune Response mentioning
confidence: 89%
See 1 more Smart Citation
“…While the second CD226 ligand, nectin 2 or CD112, has been found to be overexpressed in many cancers including lymphoblastic leukemia and squamous cell carcinomas, one study also documents the presence of soluble nectin‐2 in sera of cancer patients. Baseline serum nectin‐2 levels were found to be elevated in patients with colorectal cancer, especially at the nonmetastatic levels . All these data show that the soluble isoforms of the immune checkpoint molecules can serve as important prognostic or diagnostic markers and also present with novel immunotherapeutic strategies in cancer.…”
Section: Immune Checkpoint Molecules: Regulating the Immune Response mentioning
confidence: 89%
“…Baseline serum nectin-2 levels were found to be elevated in patients with colorectal cancer, especially at the nonmetastatic levels. 143 All these data show that the soluble isoforms of the immune checkpoint molecules can serve as important prognostic or diagnostic markers and also present with novel immunotherapeutic strategies in cancer.…”
Section: Soluble Isoforms Of the Cd226/tigit: Cd155/cd112 Costimulamentioning
confidence: 99%
“…DNAM-1 + GM NK-92 cells degranulated against all primary sarcoma explants as well as against the majority of the established cell lines, proving the potential of CD112 and CD155 as tumorspecific markers for targeted immunotherapies (Figures 3, 7). This, along with the absence of the degranulation response of NK cells against healthy donor PBMCs, showed that the use of DNAM-1 + GM NK-92 cells could be restricted/directed only to targets that had elevated CD112 and/or CD155 expression (Figures 2, 7), which is observed in tumors from various origins (65)(66)(67)(68)(69)(70)(71)(72)(73)(74)(75)(76)(77)(78)(79)(80)(81)(82)(83), including osteosarcomas (24).…”
Section: Discussionmentioning
confidence: 99%
“…So far, although only few investigations exist, the involvement of Nectin‐2 in tumor pathogenesis has been described for different tumor entities, such as breast and ovarian cancer, but also for gallbladder, colorectal or pancreatic cancer . In some of these studies, high expression of Nectin‐2 was associated with high malignancy, advanced tumor stage, poor differentiation, fast progression and poor outcome/prognosis . At the same time, inhibition of Nectin‐2 was followed by ceasing proliferation of tumor cells in cell culture.…”
Section: Introductionmentioning
confidence: 99%
“…[19][20][21] In some of these studies, high expression of Nectin-2 was associated with high malignancy, advanced tumor stage, poor differentiation, fast progression and poor outcome/prognosis. [20][21][22] At the same time, inhibition of Nectin-2 was followed by ceasing proliferation of tumor cells in cell culture. These studies indicate the high potential of Nectin-2 as a target for antibody therapeutics.…”
mentioning
confidence: 99%